Social Innovation in the Academic Curricula of Chemical Science Degrees in South Africa - Mohlala, Pheladi Junior; Msimango-Galawe, Jabulile (International Journal of African Higher Education, 2021)
Social innovation is growing internationally and is a focus area for sub- Saharan Africa. While studies have been conducted on the factors that contribute to the failure to incorporate social innovation in academic curricula, there is a paucity of such research in the South African context, especially in relation to university curricula. This qualitative study explored chemical scientists’ perceptions on the interventions required to introduce social innovation to the academic curricula of the chemical science degree in South African universities. Semi-structured interviews were conducted with 14 chemical scientists and the data was analysed using thematic analysis. The key findings included the overall lack of awareness and understanding of social innovation and the social challenges confronting South Africa. These factors hamper the development of sustainable academic curricula, effective community engagement and societal change. Furthermore, academic institutions’ reluctance to embrace change is cause for concern. Key words: Social innovation, chemical sciences, academic curriculum, South African universities